Tied Grants and Policy Reform in Hospitals and Schools - Ramamurthy, Vijaya (Federation Press, 2012)
Tied grants have long been a vehicle for Commonwealth-instigated policy reforms, providing potent opportunities to redraw constitutional lines of responsibility andaccountability, outside of formal amendments or referendums. This paper aims to cast further light on the somewhat obscure operation of these grants and how they have served to facilitate, impede and compromise major policy reforms since the mid-1970s. Drawing on a longitudinal case study examination of tied grants for public hospitals and schools, the paper reveals that the tussle over policy powers has been a dual-sided affair, with the Commonwealth's quest for extended policy influence being countered by States' defiance, delay and adjustment of national goals. Perhaps of greater significance is the simultaneous incidences of genuine intergovernmental collaboration and collusion, where national goals perceived as mutually beneficial, have been more readily adopted. The complex and often volatile policy making dynamics that has characterised the negotiation and implementation of these grants makes this a prolific policy space from which to gain both a retrospective and prospective understanding of the process of change within the Australian federal system.In particular, against the present backdrop of renewed emphasis on COAG and federal system reform, this paper argues that the use of tied grants for policy reform carries some quite distinct and inherent risks and possibilities, both of which must be better understood by policymakers at both levels of government, if this instrument is to be wielded more effectively in the pursuit of enhanced federal system performance into the future.